Synthesis of 2-(1-Benzofuran-2-yl)-4-(1,3-benzoxazol-2-yl/ 1,3-benzothiazol-2-yl) Quinolines as Blue Green Fluorescent Probes - Yadav D. Bodke; Sheelavanth Shankerrao; Hosanagara N. Harishkumar (Journal of Chemistry)
A series of novel 2-(1-benzofuran-2-yl)-4-(1,3 benzoxazol-2-yl/1,3-benzothiazol-2-yl) quinoline derivatives 4(a–d) were synthesized in one step by the reaction of 2-(1-benzofuran-2-yl) quinoline-4-carboxylic acids 3(a-b) with o-aminophenol and o-amino thiophenol, respectively, using polyphosphoric acid (PPA) as a cyclizing agent. The fluorescent properties of newly synthesized compounds were investigated in three different organic solvents like chloroform (CHCl3), tetrahydrofuran (THF), and dimethyl sulfoxide (DMSO). The photophysical constants such as quantum yield and stokes shift were determined. From the results of fluorescence study, it is evident that all synthesized compounds are fluorescent in solution. Compound 4a emitted green light (490.4 nm, 518.2 nm, and 522.4 nm) with high quantum yield in all the three solvents, while compounds 4b, 4c, and 4d emitted green light (512 nm, 499 nm, 510 nm) only in polar solvent DMSO. All fluorescent probes exhibited a bathochromic shift on increase in polarity of the solvent.